If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + (x + -9) + x = 59 Reorder the terms: 5 + (-9 + x) + x = 59 Remove parenthesis around (-9 + x) 5 + -9 + x + x = 59 Combine like terms: 5 + -9 = -4 -4 + x + x = 59 Combine like terms: x + x = 2x -4 + 2x = 59 Solving -4 + 2x = 59 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 2x = 59 + 4 Combine like terms: -4 + 4 = 0 0 + 2x = 59 + 4 2x = 59 + 4 Combine like terms: 59 + 4 = 63 2x = 63 Divide each side by '2'. x = 31.5 Simplifying x = 31.5
| F(x)=xsq+x | | 2(x+12)+7(x-5)=4x-56 | | (8x-y-7)(6x)= | | x^3=41 | | 5y+36=10y+6 | | 0=x^3-3x-6 | | 4(2r+5)=6(r-2) | | 9-11x-7-10x=5 | | 6.1-r=3.4 | | 24d+40de= | | 4(z-3)+z=-2 | | -3(y-4)=18 | | -(9x-9)+9x= | | -3(7+5n)=-96 | | -1/3(2b-6) | | 3+4x+3=-2 | | X(7x-3)=(7x+8)(x-1) | | 7(2x-3)=3+2(x+5)+7 | | 11(-9-2x)=-(12x+11) | | i+30=28 | | 4(-5+x)=48 | | 3x+8=(6-x) | | 2(x-16)-5(x-3)=18 | | 6[x-10]+8=26 | | 7z+17=6z+8 | | 16x+5=-37 | | (x+9)(x-3)=(x+1)(x+1) | | [n/10]=3 | | 8-(3+b)=b+-9 | | -[p-4]+9=8 | | -3r-6r=-9 | | 3(x-4)-4(3-x)=x+3-(x-5) |